2007
DOI: 10.1099/mic.0.2007/006379-0
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella henselae exists as a mosaic of different genetic variants in the infected host

Abstract: Bartonella henselae is a fastidious bacterium associated with infections in humans and cats. The mechanisms involved in the long-term survival of bartonellae despite vigorous host immune responses are poorly understood. Generation of genetic variants is a possible strategy to circumvent the host specific immune responses. The authors have recently demonstrated the coexistence of different genetic variants within the progeny of three primary B. henselae isolates from Berlin by PFGE analysis. Aims of the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
15
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 35 publications
3
15
2
Order By: Relevance
“…In the study by Berghoff et al., up to three genetic variants were detected within 20 (58.8%) isolates, indicating that most primary isolates display a mosaic-like structure [11]. The close relatedness of the genetic variants within an isolate was confirmed by MLST.…”
Section: Adaptation Of Bartonella Species To the Mammalian Hostmentioning
confidence: 99%
“…In the study by Berghoff et al., up to three genetic variants were detected within 20 (58.8%) isolates, indicating that most primary isolates display a mosaic-like structure [11]. The close relatedness of the genetic variants within an isolate was confirmed by MLST.…”
Section: Adaptation Of Bartonella Species To the Mammalian Hostmentioning
confidence: 99%
“…The aim of the present study was to develop a MLST scheme for B. quintana , based on the same genetic loci as those used previously for B. henselae [18], [19], [20], [21], [22]. We validated this scheme against a diverse sample of isolates representing three continents, over 60 years, and differing disease manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, Kabeya et al (9) reported variations of up to 5 bands in PFGE patterns of B. henselae isolates obtained from naturally infected cats during different bacteremic peaks. However, we have recently demonstrated that genetic variants displaying 1-to 4-band differences frequently occur within primary B. henselae isolates and do not necessarily indicate infection by a different strain (11,12). Careful interpretation of PFGE typing results, use of additional restriction endonucleases, or use of other typing techniques is necessary to ensure correct classifi cation of different patterns to the variant or strain level.…”
mentioning
confidence: 99%
“…It was concluded that the cats were persistently infected with B. henselae (8). We have recently demonstrated the appropriateness of pulsed-fi eld gel electrophoresis (PFGE) and multilocus sequence typing (MLST) for differentiation of B. henselae isolates to the strain level (10,11). Therefore, we analyzed the clonal relationship between sequential B. henselae isolates that were obtained at different times from the blood of 2 cats to determine whether recurrences were caused by the initial strain or a new strain.…”
mentioning
confidence: 99%
See 1 more Smart Citation